Pengaruh Pertumbuhan Ekonomi dan Rata-Rata Lama Sekolah Terhadap Tingkat Pengangguran di Kota Jambi Tahun 2014-2024 - Yoega Maulana Jorand; Asrini; Irmanelly (Teewan Journal Solutions, 2025)
The purpose of this study is to determine and analyze how the two variables influence the unemployment rate partially and simultaneously in Jambi City during 2014-2024. The type of research used in this study is quantitative research. The type of data used in this study is secondary data. The results of the simultaneous test show that economic growth and average length of schooling together have a significant effect on the unemployment rate in Jambi City. Then for the partial test, the results of the study show that economic growth has a significant effect on the unemployment rate in Jambi City. In addition, the results of the study also show that the average length of schooling has a significant effect on the unemployment rate in Jambi City.